Perbedaan Kualitas Seksual Wanita dengan Kontrasepsi Hormonal dan Non Hormonal di Desa Kamulyan Kecamatan Tambak - Herniyatun Herniyatun; Gea Andriani; Diah Astutiningrum (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
The Family Planning Program (KB) is aims to regulate the birth spacing of children, the ideal age to give a birth, regulate pregnancy, and carry out promotions, protections, assistance according to reproductive rights to build a happy family. Contraceptives that used in Indonesia are categorized as hormonal contraception and non-hormonal contraception. According to research, hormonal contraceptives have side effects that can reduce sexual libido. Decreased libido has affects for a person's sexual quality. Determins the The Different Of Sexual Quality In Women With Hormonal And Non Hormonal Contraceptions In Kamulyan Village Tambak District The type of this research was a quantitative research method and used a cross-sectional approach. The sample of this research was 128 respondents, which were taken using accidental sampling. Data analysis used Independent sample t-test test, with a questionnaire with 17 questions items for took a sample. Result: Independent sample t-test test showed that the average result for hormonal contraception was 62.11 and the average for non-hormonal contraception was 60.10. And p=0.030 (<0.05). There was a different of sexual quality in women between use hormonal contraception and non-hormonal contraception in Kamulyan village, Tambak district, with was p value: 0.030 (<0.05).